A multi-centered retrospective study on the efficacy of pulsed radiofrequency nerve ablation in the treatment of recalcitrant plantar fasciitis: a mid-term outcome - Kanesen, Kumarendran; Jaafar, Mohd Shahril; Alias, Azammuddin; Kam, Ming Long; Yahaya, Mohd Yusoff (Cureus, 2024)
Background Plantar fasciitis, a condition marked by persistent and often excruciating heel pain, frequently poses a formidable hurdle when conservative treatment approaches fall short. This multi-centred retrospective study embarks on a journey to explore the potential effectiveness of pulsed radiofrequency nerve ablation (RFNA), an innovative and less invasive procedure, as a novel avenue for treating recalcitrant plantar fasciitis. This investigation centres around a group of 24 patients who have faced the persistence of this challenging ailment. By meticulously scrutinizing patient outcomes and conducting a comprehensive analysis of safety aspects, this study aspires to offer enlightening revelations regarding the promise and practicality of pulsed RFNA as a therapeutic solution for tackling this intricate and tenacious condition. Methods This retrospective study included 24 patients who had undergone pulsed RFNA for recalcitrant plantar fasciitis between June 1, 2020, and June 1, 2022, at Hospital Pengajar Universiti Putra Malaysia (HPUPM), Hospital Universiti Teknologi Mara (UiTM), and Hospital Serdang. Patients were selected from the Orthopedic Clinics at HPUPM, Hospital UiTM, and Hospital Serdang and were screened according to the inclusion and exclusion criteria. Patient data was extracted from the hospital information system and electronic medical records. Pre-procedure and post-procedure assessments were conducted at one, three, and six months on the selected patients using the visual analog scale and American Orthopaedic Foot and Ankle Society Ankle-Hindfoot Scoring systems. All selected patient data was traced and tabulated accordingly. Results This study evaluates the effectiveness of pulsed RFNA in treating recalcitrant plantar fasciitis in 24 participants (39 feet). Results show a significant reduction in pain and improvement in functionality at one, three, and six months post-RFNA. Demographic factors (age, gender, and specific diagnosis) did not significantly impact outcomes. The study supports pulsed RFNA as an effective treatment for recalcitrant plantar fasciitis, emphasizing consistent benefits across various patient characteristics. Conclusion In conclusion, the study demonstrates the notable effectiveness of pulsed RFNA in improving pain reduction and functional outcomes for individuals with recalcitrant plantar fasciitis. The findings, consistent across various demographic factors, support pulsed RFNA as a promising and uniform treatment option for those who do not respond to conservative measures.